Surface-enhanced Raman scattering on a silver film-modified Au nanoparticle-decorated SiO2 mask array. Issue 81 (3rd September 2015) - Chang, Chi-Ching; Chen, Liang-Yih; Yang, Kuang-Hsuan; Chen, Qing-Ye; Liang, Yu-Chih; Lin, Shyr-Yi; Liu, Yu-Chuan
<x xml:space="preserve">Abstract</x> SERS of R6G absorbed on this developed array exhibits a higher intensity by ca. 30-fold, as compared with that of R6G absorbed on the Au NP-based array without the modification of Ag films.